CODE MIXING AS LANGUAGE STYLE IN COMMUNICATION THROUGH SOCIAL MEDIA TWITTER - Meliani, Putu Ega; Ratminingsih, Ni Made; Mahendrayana, Gede (Yavana Bhasha : Journal of English Language Education, 2021)
This paper aims to recognize the types of code-mixing and factors influencing code-mixing by Twitter users. This study uses a descriptive qualitative research design. The subject of this study is Twitter users who post tweets that contained code-mixing. The researcher uses documentation and interview as data collection methods. The data for identifying the types of code-mixing were collected by documenting the tweets posted previously by Twitter users on the Twitter platform. The interview guide was used to ask questions to respondents about the factors influencing the use of code-mixing in communication as language style.Â  The data were analyzed through three stages: data reduction, data display, and conclusion: verifying. The data collected from documentation and interview showed that insertion code-mixing became the dominant type used among Twitter users. It is influenced by several factors from within of language speaker and external factors.